Prone Positioning of Patients with Cervical Spine Pathology - Sarah L. Boyle; Zoe Unger; Vinay Kulkarni; Eric M. Massicotte; Lashmi Venkatraghavan (Journal of Neuroanaesthesiology and Critical Care, 2019)
Patients with cervical trauma or degenerative disease often require surgical decompression and stabilization in the prone position and are at the risk of secondary neurological injury during this transfer. This review aims to explore the current literature on different methods of positioning patients prone and to identify the safest technique to achieve prone positioning in patients with an unstable cervical spine undergoing posterior cervical spine surgery. We searched the Embase, Medline, and Medline-in Process databases for literature in English related to prone positioning patients with cervical spine pathology undergoing spine surgery. Seventy-three citations were identified as relevant and reviewed in detail with 20 articles being identified as answering the clinical questions posed. Our literature review identified three methods of prone positioning patients with cervical pathology: logroll with manual in-line stabilization (MILS), rotating the patient on a specialized spinal table using a “sandwich and flip” technique, and awake prone positioning. Each of these methods has its own advantages and disadvantages. When comparing the degree of neck movement between positioning techniques, “sandwich and flip” rotation was associated with over 50% reduction in both flexion–extension and axial–lateral rotation as compared to logroll with MILS. Awake self-positioning of a patient is another alternative that allows for rapid neurological assessment after repositioning. A “sandwich and flip” is the safest way to turn a patient with cervical pathology into a prone position for surgery. For cooperative patients, who are physically capable, awake self-positioning is a good alternative.